Correction: Effect of a new formulation of micronized and ultramicronized N-palmitoylethanolamine in a tibia fracture mouse model of complex regional pain syndrome. - Roberta Fusco; Enrico Gugliandolo; Michela Campolo; Maurizio Evangelista; Rosanna Di Paola; Salvatore Cuzzocrea (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0178553.].